An Early Pleistocene interglacial deposit at Pingorsuit, North‐West Greenland. (29th August 2022) - Bennike, Ole; Colgan, William; Hedenäs, Lars; Heiri, Oliver; Lemdahl, Geoffrey; Wiberg‐Larsen, Peter; Ribeiro, Sofia; Pronzato, Roberto; Manconi, Renata; Bjørk, Anders A.
Abstract : At the Pingorsuit Glacier in North‐West Greenland, an organic‐rich deposit that had recently emerged from the retreating ice cap was discovered at an elevation of 480 m above sea level. This paper reports on macrofossil analyses of a coarse detritus gyttja and peaty soil, which occurred beneath a thin cover of till and glacifluvial deposits. The sediments contained remains of vascular plants, mosses, beetles, caddisflies, midges, bryozoans, sponges and other invertebrates. The flora includes black spruce, tree birch, boreal shrubs and wetland and aquatic taxa, which shows that mires, lakes and ponds were present in the area. We describe a new extinct waterwort species Elatine odgaardii . The fossils were deposited in a boreal environment with a mean July air temperature that was at least 9 °C higher than at present. The fossil assemblages show strong similarities with others from Greenland that have been assigned an Early Pleistocene age, and we suggest a similar age for the sediments found at the margin of the Pingorsuit Glacier. At the Pingorsuit Glacier in North‐West Greenland, an organic‐rich deposit was discovered at an elevation of 480 m above sea level. The sediments contained remains of vascular plants, mosses, beetles, caddisflies, midges, bryozoans, sponges and other invertebrates. The fossils were deposited in a boreal environment with a mean July air temperature that was at least 9 °C higher than at present.